(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: The increasing prevalence of term premature rupture of membranes (PROM) poses significant challenges to obstetrical management, necessitating enhanced predictive methodologies for optimal clinical outcomes. Objectives: Primary Objective: To evaluate the association between amniotic fluid index (AFI) and mode of delivery, as well as fetomaternal outcomes, in pregnant women at term with PROM. Specific Objectives: To assess the association between AFI values at admission and the mode of delivery (vaginal vs. cesarean) in Term PROM cases. • To determine whether low AFI (AFI < 5 cm) is a predictive marker for induction failure and higher cesarean delivery rates. • To explore potential indications for cesarean delivery in relation to AFI status, including fetal distress and failed induction. Materials and Methods: This analytical cross-sectional study was conducted at Dhaka Medical College, Bangladesh, from August 2019 to February 2020. A total of 126 pregnant women with confirmed term PROM (37–40 weeks) were enrolled. Inclusion criteria were singleton cephalic pregnancies with adequate pelvis; exclusions included preterm PROM, previous uterine surgery, non-cephalic presentation, intrauterine growth restriction (IUGR), and maternal hypertensive or diabetic disorders. AFI was measured by ultrasound and patients were grouped as Group A (AFI e” 5 cm) and Group B (AFI < 5 cm). After PROM confirmation, patients were monitored for spontaneous labor for 24 hours; if labor did not begin, induction was performed based on cervical status. Outcomes included mode of delivery and fetomaternal complications. Data were analyzed using SPSS version 22 with chi-square tests for categorical variables; p < 0.05 was considered significant. Results: Among 126 term PROM cases, 76 had AFI e” 5 cm (Group A) and 50 had AFI < 5 cm (Group B). Vaginal delivery occurred in 50 women in Group A (65.8%), of which 26 had spontaneous onset of labor and 14 required induction. In Group B, only 5 women (10%) delivered vaginally, with 1 spontaneous and 4 induced labors. Cesarean section rates were significantly higher in Group B (90.0%) compared to Group A (34.2%) (p = 0.002), primarily due to fetal distress and failed induction. Induction outcomes showed that successful vaginal delivery after induction was 77.8% in Group A versus 25% in Group B (p = 0.003). Neonates in Group B had increased need for resuscitation (38.0% vs. 10.5%, p = 0.02) and higher rates of complications including pneumonia, respiratory distress syndrome, neonatal sepsis, hypoglycemia, and other complications. The proportion of neonates without complications was significantly lower in Group B (34.0%) compared to Group A (71.1%) (p = 0.01). Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 13-18